Baseline characteristics and management of patients with atrial fibrillation/flutter in the emergency department: results of a prospective, multicentre registry in China. Issue 8 (August 2014) - Zhang, H.; Yang, Y.; Zhu, J.; Shao, X.; Liu, Y.; Zhao, L.; Yu, P.; Zhang, H.; He, Q.; Gu, X.
Abstract Background/Aim There have been several studies of atrial fibrillation (AF) over the past decades; however, data from Chinese patients are scarce. The aim of the study was therefore to describe the patient characteristics, risk profile and management strategies for Chinese AF patients presenting to emergency department (ED). Methods We conducted a prospective, multicentre registry of patients with AF or atrial flutter (AFL) in China. Participants were enrolled at 20 EDs, then data regarding baseline characteristics and treatment in EDs were collected. Results Of the 2016 Chinese patients, 1104 (54.8%) were female. Six hundred eighteen (30.7%) had paroxysmal AF, 452 (22.4%) had persistent AF and 945 (46.9%) had permanent AF. The most common comorbidity was hypertension (55.5%), followed by coronary artery disease (41.8%) and heart failure (HF, 37.4%). The prevalence of concomitant cardiovascular risk factors, such as HF and valvular heart disease, increased as AF progressed. Among the patients with non‐valvular AF, 110 (12.7%) of those with CHADS2 (congestive HF, hypertension, age of 75 years and greater, diabetes mellitus and history of stroke) ≥2 were prescribed oral anticoagulants (OAC), while 119 (15.6%) of those with CHADS2 <2 received such agents. Among the 324 patients with valvular AF, 134 (41.4%) actually were treated with OAC. The international normalised ratio value was within the target range (2.0–3.0) in 96 patients only (26.4%). Moreover, a total of 16.2% of the patients received ≥1 anti‐arrhythmic agents, whereas rate control agents were used more frequently (68.4%). Conclusions According to the present study, the risk profile and management of Chinese patients with AF/AFL differed from that observed in previous studies. The use of OAC inadequately deviate from current guidelines.